Neuroimaging of temporomandibular disorders (a clinical case) - Savychuk, N. O.; Pekhno, V. V.; Liakhovska, A. V.; Riebienkov, S. O.; Riabko, I. B. (Regulatory Mechanisms in Biosystems, 2025)
This study add s information about the neural mechanisms underlying temporomandibular disorders (TMD) using stru c tural and functional magnetic resonance imaging (MRI, fMRI). The aim was to analyse the relationship between the functional state of the brain and pathological changes in the joint. The study included a comprehensive clinical and instrumental examin a tion, which included the registration of the central ratio of the jaws after using the Kois deprogrammer, as well as the use of fMRI data processing methods followed by statistical and cluster processing of the results. Structural MRI revealed degener a tive changes in the temporomandibular joint (TMJ), such as articular disc displacement, degeneration and soft tissue edema . fMRI revealed activation of brain regions associated with motor control and sensory feedback, specifically in the precentral and postcentral gyrus (Brodmann area 6, 3, 43) and insular crust (Brodmann area 13). The results of the comparative analysis proved a correlation between the functional state of the brain and pathological changes in the joint, which indicates the pre s ence of compensatory mechanisms of the central nervous system. The results demonstrate the importance of an integrated approach to the treatment of patients with TMD using modern diagnostic methods. Thus, the results of the clinical case co n firm the effectiveness of using neuroimaging techniques to diagnose the central mechanisms of TMJ function regulation , open up prospects for further research in this area, and provide an example of processing data in patients with TMD. Determining changes in brain activity could help provide a more accurate assess ment of the effectiveness of therapeutic interventions and improve the prognosis of the disease. Further research may be aimed at developing personalized approaches to the treatment of TMD, taking into account the individual characteristics of brain activity.